Proses Pembelajaran Penjasorkes Dalam Situasi Pandemi Covid-19 Pada Siswa Kelas XI SMA N 1 Paguyangan (Universitas Negeri Semarang, 2021)
The Covid-19 pandemic has an impact on all sectors, one of which is the education sector. In the education sector the learning process is carried out online. Penjasorkes is one of the subjects affected by online learning. For this reason, the problem of this research is how the physical education learning process in the Covid-19 pandemic situation in class XI students of SMA N 1 Paguyangan. The purpose of this study was to determine the physical education learning process which includes the planning, implementation, and evaluation processes in the Covid-19 pandemic situation in class XI students of SMA N 1 Paguyangan. This research uses qualitative research methods with a descriptive approach. The results of his research are the planning process is carried out by making a syllabus and RPP PJJ (Distance Learning), the implementation of physical education learning is carried out asynchronously with the help of google classroom, and the assessment process is carried out through three aspects, namely affective, cognitive, and psychomotor aspects. The conclusion of this research is that the physical education learning process in the Covid-19 situation in class XI SMA N 1 Paguyangan is good enough.